Mechanisms mediating effects of cardiotonic steroids in mammalian blood cells - Poluektov, Yuri M.; Lopina, Olga D.; Strelkova, Maria A.; Kuleshova, Iuliia D.; Makarov, Alexander A.; Petrushanko, Irina Yu. (Frontiers in Pharmacology, 2025)
Cardiotonic steroids (CTSs) were known as steroidal plant compounds that exert cellular effects by the binding to Na,K-ATPase. Earlier, plant (exogenous) CTSs were used to treat chronic heart failure. By now, endogenous CTS have been identified in mammals, and their concentrations in the blood, normally in a subnanomolar range, are altered in numerous pathologies. This indicates their role as endogenous regulators of physiological processes. CTS transport occurs primarily in the blood, yet the CTS effects on blood cells remain poorly understood. This review summarizes the CTS effects on blood cells of animals and humans under normal and pathological conditions, and analyzes their action based on known mechanisms of action in mammalian cells. At high concentrations (greater than 10−9 M), CTS binding to Na,K-ATPase inhibits the enzyme, whereas lower concentrations of CTSs induce signaling cascades or activate the enzyme. All these mechanisms are shown to be present in blood cells. The particular CTS effect is determined by the CTS type, its concentration, the isoform composition of the catalytic α-subunit of Na,K-ATPase in the cell, and other cell features. It has been demonstrated that all blood cell types (erythrocytes, leukocytes, and platelets) expressed both ubiquitously distributed α1-isoform and tissue-specific α3-subunit, which exhibits a different ion and CTS affinity compared to α1. This results in a wide spectrum of blood cell responses to fluctuations in CTS levels in the blood. In particular, an increase in the level of endogenous CTSs by a more twofold is sufficient to induce a decline in the activity of erythrocyte Na,K-ATPase. The administration of exogenous CTSs is able to modulate the proinflammatory activity of leukocytes, which is attributed to the activation of signaling cascades, and to exert an influence on platelet activation. Hence, alterations of CTS levels in bloodstream significantly affect the functionality of blood cells, contributing to the organism’s adaptive response. On top of this, a comparison of the effects of CTSs on human leukocytes and rodent leukocytes carrying the CTS-resistant α1-isoform often reveals opposite effects, thus indicating that rodents are an unsuitable model for studying CTS effects on these cells.